Augmented Reality (AR) Solar System Objects Based on Marker-Based 3D - Zaki, Naufal; Majid, Nur Kholis (CoreID Journal, 2023)
This research implements Augmented Reality (AR) technology in solar system learning using a marker-based 3D object recognition method. The aim of this research is to create an interactive and immersive experience for users to learn about the solar system through an Android smartphone. The research development method follows the waterfall approach, which includes requirements analysis, system and software design, implementation, integration, testing, and maintenance. This AR application utilizes marker-based 3D object recognition technology on an Android smartphone. The test results demonstrate the success of the application in displaying 3D objects during the scanning process using marker cards. Distance testing indicates that the optimal range for recognizing solar system objects is 20-30 cm. Meanwhile, light intensity testing reveals that outdoor daylight conditions with an intensity of 90-120 Lux provide optimal results. In conclusion, this research successfully develops an application for recognizing solar system objects using AR technology. The application offers an interactive learning experience for the solar system. The utilization of the waterfall method and the positive test results are the strengths of this research. For future development, the consideration of employing the scrum method can accelerate the application development and testing processes.